Feria "La Calle es Mía" y su aporte al turismo cultural en el cantón Babahoyo - MARTINEZ PAZ, MARIA CRISTINA (2024)
The purpose of this research is to analyze the initial impact of the "La Calle es Mía" Fair in the local community of Babahoyo. In the methodology of this study, a qualitative and documentary approach was implemented in which a survey was applied to the participants of the fair, in order to identify its initial impact on the local community and describe the tourist elements that make it up. The results showed that the majority of visitors are satisfied with the organization of the fair and highlighted a good level of execution and planning. In addition, a large number of Fair participants experienced improvements in the local economy, reflecting a positive impact on the economic growth of the community, also highlighting the appreciation of ethnic and cultural diversity. These aspects were considered fundamental to promote tourism in the Babahoyo canton, offering authentic experiences that reflect the local cultural wealth.